FRI0365 New collagen biomarkers predict progression of fibrosis in systemic sclerosis. (15th June 2017) - Dobrota, R; Jordan, S; Juhl, P; Maurer, B; Wildi, L; Bay-Jensen, A-C; Karsdal, MA; Siebuhr, AS; Distler, O
Abstract : Background: Systemic sclerosis (SSc) is a complex autoimmune disease with extensive fibrosis of the skin and internal organs in which extracellular matrix (ECM) remodeling is a key pathogenic process. Imbalance in the formation and degradation of collagens results in fibrosis. Quantifying the tissue turnover in a highly fibrotic disease such as SSc is very important for the prediction of disease progression and therapeutic efficacy. Given the clinical heterogeneity of SSc patients, biomarkers facilitating personalized medicine approaches are highly needed. Objectives: To evaluate the potential of selected ECM neo-epitopes as serological biomarkers for diagnosis, prediction of clinical outcomes and disease progression in SSc. Methods: Healthy controls (HC; n=29), stable SSc (n=149), and progressive SSc patients (n=23, progression defined either as 10% decrease in FVC% predicted or increase in mRSS ≥25% and 5 points on one year clinical follow up), meeting the 2013 ACR/EULAR classification criteria were analyzed. Longitudinal clinical assessment, data recording and sera collection were done according to EUSTAR standards. ECM-degradation (C3M, VICM, C4M2, BGM) and ECM-formation biomarkers (P1NP, P4NP7S, Pro-C3, Pro-C5, Pro-C6) were measured in serum using newly developed ELISA-based assays (Nordic Bioscience). Differences in biomarker levels were analyzed with respect to several fibrosis-related clinical outcomes. Statistical analysis was performed by Man-Whitney U, Kruskal-Wallis and Spearman tests. Biomarkers' sensitivity and specificity was examined by ROC analysis. Results: Both ECM-degradation and ECM-formation biomarkers differed between SSc patients and HC: The expression of C4M2, Pro-C3, BGM and C3M was significantly increased in SSc patients compared to HC (p<0.0001, AUC=0.93; p<0.0001, AUC=0.74; p=0.003, AUC=0.67; p<0.0001; AUC=0.94, respectively), whereas P1NP was significantly lower (p<0.0001, AUC=0.78), Figure 1 . Furthermore, Pro-C3, VICM and Pro-C6 levels were significantly higher in SSc progressors vs. HC (p<0.0001, AUC=0.86; p=0.003, AUC=0.75; p=0.0005, AUC=0.81, respectively). Currently, there is no fully validated biomarker predicting worsening of fibrosis. In this regard, most interestingly, the ECM-degradation markers C4M2, BGM, C3M were significantly lower in SSc patients showing progression of fibrosis on follow up versus SSc patients being stable on follow up (p<0.0001; p<0.008; p<0.0001, respectively). Consistently, the formation marker Pro-C6 was significantly increased (p=0.001, AUC=0.71) indicating a profound imbalance of ECM turnover in progressors. The strongest difference between progressive and stable SSc patients was seen for the ratio between the formation and degradation biomarkers Pro-C3/C3M which showed an AUC of 0.86 in progressive vs. stable SSc patients (p<0.0001). Conclusions: These data support ECM neo-epitopes as potential new biomarkers of prognostic interest in SSc. This could help identifying patients at risk of progression of their fibrotic disease at one year follow up. The significant decrease in ECM-degradation markers in SSc progressors compared to stable patients suggests an impairment of collagen degradation in this group. The ratio of Pro-C3/C3M is as a new potential predictive index for differentiation of stable vs. progressive patients. Disclosure of Interest: R. Dobrota: None declared, S. Jordan: None declared, P. Juhl Employee of: Nordic Bioscience, B. Maurer: None declared, L. Wildi: None declared, A.-C. Bay-Jensen Employee of: Nordic Bioscience, M. A. Karsdal Shareholder of: Nordic Bioscience, Employee of: Nordic Bioscience, A. S. Siebuhr Employee of: Nordic Bioscience, O. Distler Grant/research support from: Actelion, Bayer, Boehringer Ingelheim, Pfizer, Sanofi, Consultant for: 4D Science, Actelion, Active Biotec, Bayer, BiogenIdec, BMS, Boehringer Ingelheim, ChemomAb, EpiPharm, espeRare foundation, Genentech/Roche, GSK, Intentiva, Lilly, medac, Mepha, MedImmune, Mitschubishi Tanabe Pharma, Pharmacyclics, Pfizer, Sanofi, Serodapharm, Sinoxa, Speakers bureau: AbbVie, iQone Healthcare, Mepha